The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1185/030079900750120269
|View full text |Cite
|
Sign up to set email alerts
|

Marked Effect of Octreotide Acetate in a Case of Pancreatic Pleural Effusion

Abstract: A pancreaticopleural effusion is a rare complication of chronic pancreatitis. Fasting, a protease inhibitor, and/or a surgical intervention are generally selected for the treatment of the pancreatic effusion. We reported here the case, in which octreotide acetate was effective for resolving pancreatic effusion. A 67-year-old man was admitted with a massive pleural effusion. This effusion contained a high level of amylase. Endoscopic retrograde pancreatography followed by computed tomography revealed a pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…CT has also been successful in identifying pancreaticopleural fistulas, although it is was less sensitive (43%) compared to ERCP (79%) in this review. Performing CT immediately after ERCP has been reported to increase the sensitivity of CT in detecting pancreaticopleural fistulas (8), presumably because of the contrast injected directly in the pancreatic duct at the time of ERCP. Recently, MRCP has been shown to be useful in making the diagnosis (4,5,10,12,15).…”
Section: Discussionmentioning
confidence: 99%
“…CT has also been successful in identifying pancreaticopleural fistulas, although it is was less sensitive (43%) compared to ERCP (79%) in this review. Performing CT immediately after ERCP has been reported to increase the sensitivity of CT in detecting pancreaticopleural fistulas (8), presumably because of the contrast injected directly in the pancreatic duct at the time of ERCP. Recently, MRCP has been shown to be useful in making the diagnosis (4,5,10,12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple different approaches have attempted to produce reconstituted skin with hair in mouse and humans. [1] In the mouse, we demonstrated that dissociated epidermal and dermal cells from newborn mouse skin self-assemble in vitro into multi-layered skin organoids containing placodes and dermal condensates, the two stem cell populations necessary for hair follicle development. [2,3] When grafted onto a full thickness dermal wound on a nude mouse, the cultured organoids formed mature, cycling hair follicles within a planar skin configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Aproximadamente, 5% dos pacientes com PC irão desenvolver derrame pleural, que geralmente ocorre após o episódio agudo da doença ou até mesmo sem nenhuma história prévia de pancreatite. A maioria dos pacientes com derrame pleural decorrente de PC pancreático é do sexo masculino e, em mais de 90% dos casos, apresenta história de etilismo crônico (3,4,6) . Esses derrames tendem a ser recorrentes, são exsudativos, com níveis elevados de amilase no líqui-do pleural, apresentando coloração acastanhada bastante característica e de grande importância para o diagnós-tico de derrames pleurais decorrentes de patologias pancreáticas (2,3,6) .…”
Section: Discussionunclassified
“…De outra forma, menos provável, esse líquido abriria caminho pelo retroperitônio, passando pelo hiato esofágico ou aórtico, e atingiria o mediastino, resultando em mediastinite, a qual poderia estender-se para uma ou ambas as cavidades pleurais. Outras vezes, poderia existir uma comunicação direta do PC com o espaço pleural pelo diafragma (1)(2)(3)(4)6) .…”
Section: Discussionunclassified
See 1 more Smart Citation